A novel JAK/ROCK inhibitor, CPL409116, demonstrates potent efficacy in the mouse model of systemic lupus erythematosus - Maria Dulak-Lis; Anna Bujak; Kamila Gala; Martyna Banach; Urszula Kędzierska; Joanna Miszkiel; Joanna Hucz-Kalitowska; Michał Mroczkiewicz; Bartosz Stypik; Krzysztof Szymczak; Paweł Gunerka; Krzysztof Dubiel; et al. (Elsevier, 2021)
Systemic lupus erythematosus is a chronic inflammatory disease, in which treatment is still limited due to suboptimal efficacy and toxicities associated with the available therapies. JAK kinases are well known to play an important role in systemic lupus erythematous. There is growing evidence that ROCK kinases are also important in disease development. In this paper, we present the results of the development of CPL409116, a dual JAK and ROCK inhibitor. The studies we performed demonstrate that this molecule is an effective JAK and ROCK inhibitor which efficiently blocks disease progression in NZBWF1/J mouse models of systemic lupus erythematous.